The Moral Compass of Companies : Business Ethics and Corporate Governance as Anti-Corruption Tools - Sullivan, John D. (International Finance Corporation, Washington, DC, 2016)
This publication targets private sector stakeholders who want to reduce a company s risk and vulnerability to corruption. It aims to provide guidance and recommendations for integrating ethics programs into corporate governance mechanisms to safeguard against corruption. Anti-corruption attitudes have changed significantly over the past two decades. Corruption is no longer regarded as a subject to be avoided and is now widely condemned for its damaging effect on countries, industries, governments, and the livelihoods of individual citizens. More importantly, the view of the private sector in the corruption equation is changing. Companies are no longer viewed only as facilitators of corruption - they are increasingly recognized as victims and a valuable source of working solutions, and anti-corruption efforts seen as integral to good corporate governance, Predictable, competitive, and fair economic environments free of corruption are central to sustainable business, economic growth and national development. It has been an easier task to raise this awareness than to reduce the corrosive effects of corruption, especially its worst manifestation of state capture. And though the challenge defies simple solutions, significant progress is being made. Today we have in place numerous international conventions and global collective action initiatives that set higher standards of transparency and accountability in corporate and public governance. More importantly, such standards are buttressed by a growing convergence of ethical values that set the tone for 'doing the right thing' in both the public and private sectors.